2018
DOI: 10.1159/000494479
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 Mitigates the Loss of Human Spermatozoa Motility by Promoting mROS Elimination

Abstract: Background/Aims: To demonstrate the function of uncoupling protein 2 (UCP2) in the regulation of human spermatozoa motility. Methods: Semen samples were collected from donors with either normal spermatozoa motility (normospermia [NS]) or poor spermatozoa motility (asthenospermia [AS]). UCP2 protein in spermatozoawas quantified by Western blotting. The level of mitochondrial reactive oxygen species (mROS) was evaluated by MitoSOX Red. The activity of mitochondrial membrane potential (MMP) in spermatozoa was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…It has been reported that a testis-specific mouse TFAM isoform lacks the mitochondrial targeting sequence and is present only in the nucleus of spermatocytes and elongating spermatids [ 57 ]. Our observations about significant increase in the level of Ucp2 in spermatozoa from both stressed and adrenaline-stimulated spermatozoa [ 14 ] could be a possible explanation for findings of other authors showing that the presence of UCP2 mitigates the loss of human spermatozoa motility [ 32 ]. Since the transcripts for main markers ( Mfn1 , Mfn2 , Opa1 ) of mitochondrial fusion/architectures, important for homeostasis of mitochondrial network and functionality [ 35 , 36 , 40 ], were dramatically increased in spermatozoa from stressed rats, these results may explain results of other authors showing the positive relation of the expression level of MFN2 with motility and cryoprotective potential of human sperm [ 33 ], as well as mitofusin-mediated promotion of OXPHOS [ 58 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that a testis-specific mouse TFAM isoform lacks the mitochondrial targeting sequence and is present only in the nucleus of spermatocytes and elongating spermatids [ 57 ]. Our observations about significant increase in the level of Ucp2 in spermatozoa from both stressed and adrenaline-stimulated spermatozoa [ 14 ] could be a possible explanation for findings of other authors showing that the presence of UCP2 mitigates the loss of human spermatozoa motility [ 32 ]. Since the transcripts for main markers ( Mfn1 , Mfn2 , Opa1 ) of mitochondrial fusion/architectures, important for homeostasis of mitochondrial network and functionality [ 35 , 36 , 40 ], were dramatically increased in spermatozoa from stressed rats, these results may explain results of other authors showing the positive relation of the expression level of MFN2 with motility and cryoprotective potential of human sperm [ 33 ], as well as mitofusin-mediated promotion of OXPHOS [ 58 ].…”
Section: Discussionsupporting
confidence: 56%
“…Human sperm motility and viability are regulated by mitophagy [ 31 ]. The loss of human spermatozoa motility is mitigated by UCP2 (uncoupling protein 2) [ 32 ], while the motility and cryoprotective potential of human sperm is connected with the MFN2 (mitofusin 2) expression level [ 33 ]. According to everything mentioned above, the mitochondria are a crucial organelle for spermatozoa functionality, and their homeostasis strongly correlates with (sub/in)fertility [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with findings that TFAM is associated with the reduction in mtDNA content of human sperm 34 and that TFAM gene expression positively correlate with abnormal forms, sperm DNA fragmentation and mtDNA copy number 35 , 36 . Our results showing that combination β-ADRs-antagonist-propranolol + β-ADRs-agonist-isoproterenol significantly decreased the level of Ucp2 suggest the positive involvement of β-ADRs in Ucp2 regulation and could be possible explanation for findings that UCP2 mitigates the loss of human spermatozoa motility 38 . The effects of β-ADRs-agonist-isoproterenol were not always in parallel with the effects of adrenaline mediated through β-ADRs and β-ADRs-antagonist-propranolol was not always diminished/abolished the effects of isoproterenol.…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown that TFAM is associated with the reduction in mtDNA content of human sperm 34 and that TFAM gene expression positive correlate with abnormal forms, sperm DNA fragmentation and mtDNA copy number 35,36 . Besides, mitophagy may be regulating human sperm function such as motility and viability 37 , UCP2 mitigates the loss of human spermatozoa motility 38 , while the expression level of MFN2 is related to motility and cryoprotective potentials of human sperm 39 . Accordingly, the mitochondria are a key organelle for sperm motility and strongly correlate with (in)fertility 21 .…”
mentioning
confidence: 99%
“…Furthermore, it was reported that the loss of sperm motility due to oxidative stress can also be consequence of reduced activity of protein that functions as ROS eliminator such as uncoupling protein 2 in the human sperm. [ 15 ] This is confirmed by cervical mucus penetration assay in which H 2 O 2 -treated sperm cells were unable to penetrate cervical mucus as good as untreated control. The cervical mucus contains proteins such as catalase that are important for sperm survival that can bind to the sperm cell to eliminate oxidative attack.…”
Section: Discussionmentioning
confidence: 74%